The Role Of Digitalization In The Development Of Small Business - Ismoilov, Botir Mukhamedovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Annotation This article scientifically analyzes the role and importance of digitalization processes in the development of small business. The study highlights the impact of digital technologies on the activities of small business entities, in particular, the effectiveness of business process automation, e-commerce, digital payment systems, and customer relationship management mechanisms. Also, based on international and national experience, the role of digitalization in increasing the competitiveness of small businesses, reducing costs, and expanding market access opportunities is substantiated. The article also considers the problems arising in the process of digital transformation, including limited financial resources, a shortage of digital infrastructure, and qualified personnel. The results of the study indicate the need for consistent development of digitalization in the small business sector.